Moving average filter for ripple current elmination - Siti Intansyafinaz, Abdul Kadir (2012)
In power electronics field concerning power converter applications; current control is becoming one of the key research areas. Typically, in current control applications, the inductor current is shaped to closely follow its reference. This is achieved by regulating the current via current control strategies. The rapid switching of the power semiconductor devices will forms the ripples on the regulated current. In analysis stage, for proper comparison between the regulated current and reference current, it is crucial that the current ripples are eliminated. Common fixed cut-off frequency filter, however, is not suitable in this application due to variable switching frequency nature of some current control techniques. Therefore, in this project, a variable cut-off frequency filtering technique based on numerical algorithm is developed to eliminate the current ripple without destroying the non-ripple data. To verify its performance, the algorithm is tested on several real data of regulated current. Result shows that the algorithm is able to filter the ripple current satisfactorily.